1997
DOI: 10.1038/sj.gt.3300533
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antitumor immune response generated by treatment of murine tumors with recombinant adenoviruses expressing HSVtk, IL-2, IL-6 or B7-1

Abstract: In a cancer gene therapy model recombinant adenoviruses challenge with wild-type tumor but not from challenges with expressing the herpes simplex virus thymidine kinase an unrelated syngeneic tumor cell line. Since cytotoxic T (HSVtk) gene were injected into tumors in situ, either alone lymphocyte responses in this tumor model were weak, we or in combination with adenoviruses (Avs) engineered to analyzed cytokine secretion from spleen cells of treated express IL-2, IL-6 or the costimulatory molecule B7-1.anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…9,10 More recent studies have further demonstrated that HSVtk + GCV therapy can lead to the induction of a Th1 immune response that may play a role in the observed antitumor immunity. 11,12 Therefore, to extend our previous work towards a more direct immunomodulatory gene therapy approach, we considered in situ adenovirus-mediated IL-12 gene transduction as a therapy for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 More recent studies have further demonstrated that HSVtk + GCV therapy can lead to the induction of a Th1 immune response that may play a role in the observed antitumor immunity. 11,12 Therefore, to extend our previous work towards a more direct immunomodulatory gene therapy approach, we considered in situ adenovirus-mediated IL-12 gene transduction as a therapy for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of tk-or CD-transduced tumors with GCV or 5-FC in many instances produced similar antitumor immunity as immunization with radiation-or drug-treated tumor cells, 39,40 only weak or no CTL activity after prodrug treatment of tumors 37,41,42 and incomplete 29,39 or no 43,44 protective immunity. ADEPT, in contrast, generated long-lasting systemic antitumor immunity that could not be generated by immunization of radiation-treated tumor cells even with addition of immunoenzyme (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In some immunocompetent animal models of HCC, a distant bystander effect relying on the activation of the immune system has been described, which synergizes with the direct elimination of tumor cells. [114][115][116][117] HSV-TK/GCV treatment has been extensively experienced in vitro and in animal models either with tumors obtained following injection of HCC lines or chemically induced HCC as shown in DEN-induced HCC in the rat model. 104,118 In this last model, using adenoviral vectors to transfer the HSV-TK gene, we have shown that a unique intratumoral injection of the viral vector with daily administration of GCV allows strong reductions of large-size tumors.…”
Section: Using Apoptosis To Program the Cell Deathmentioning
confidence: 99%